2004
DOI: 10.1093/geront/44.4.489
|View full text |Cite
|
Sign up to set email alerts
|

Consumer-Directed Community Care: Race/Ethnicity and Individual Differences in Preferences for Control

Abstract: Study findings suggest that consumer direction occurs along a continuum, with elders desiring control over some service areas but not others, and the importance of recognizing heterogeneity within racial/ethnic groups regarding consumer-directed care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 13 publications
0
27
0
1
Order By: Relevance
“…There is some evidence that good support in the form of training and assistance with administrative and accounting tasks may increase older people's acceptance of and preparedness to enrol in a CDC programme (Sciegaj et al . , Foster et al . , Simon‐Rusinowitz et al .…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that good support in the form of training and assistance with administrative and accounting tasks may increase older people's acceptance of and preparedness to enrol in a CDC programme (Sciegaj et al . , Foster et al . , Simon‐Rusinowitz et al .…”
Section: Introductionmentioning
confidence: 99%
“…This generalization, mirrored by an adaptive behavior of the older population, can explain the lower complaint and higher satisfaction rates of older persons within the health care system, even if there is no objective or rational justification for such behavior. This analysis is supported by the works of other scholars, for e.g., Sciegaj et al (2004), have argued that, traditionally, older people were not empowered to direct their own care, primarily because service providers and policy makers made assumptions about their level of interest and ability to exercise control.…”
Section: Older Persons and Complaints To Hmosmentioning
confidence: 65%
“…Unsurprisingly, self-directed support is of particular interest to those who are dissatisfied with the services they are currently receiving, or who believe that their needs are only partially being met (Department of Health and Ageing 2012, Loughlin et al 2004, Mahoney et al 2002. Also, preferences vary among age groups in relation to the preferred model of support and the degree to which they would like control over their support (Adams & Drake 2006;Sciegaj et al 2004) or the support of the person they are caring for (Putnam et al 2010). Also, preferences vary among age groups in relation to the preferred model of support and the degree to which they would like control over their support (Adams & Drake 2006;Sciegaj et al 2004) or the support of the person they are caring for (Putnam et al 2010).…”
Section: Benefits Of Self-directed Supportmentioning
confidence: 99%
“…Research has demonstrated that consumers and caregivers vary in terms of their interest in managing the support received (Alakeson 2007;Duffy 2007a;Mahoney, Simon-Rusinowitz, Loughlin et al 2004;Olinzock 2004;Putnam et al 2010;Sciegaj et al 2004) and that over time, people may change their mind regarding the amount of control they desire (Putnam et al 2010; The State of Queensland 2012). Research has demonstrated that consumers and caregivers vary in terms of their interest in managing the support received (Alakeson 2007;Duffy 2007a;Mahoney, Simon-Rusinowitz, Loughlin et al 2004;Olinzock 2004;Putnam et al 2010;Sciegaj et al 2004) and that over time, people may change their mind regarding the amount of control they desire (Putnam et al 2010; The State of Queensland 2012).…”
Section: Challenges Of Self-directed Supportmentioning
confidence: 99%